Preparation of the Epoxy / Chicken Eggshell Composites to use in Surfaces Coating - H. Jassim, Widad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this work , impact strength and the water absorption ratio of powders of white and brown local chicken eggshell reinforced epoxy with different volume fractions ( 1 , 2 , 3 , 4 and 5 % ) were studied . The experimental results show that composite filled by ( 1 % Vol . )of white eggshell powder exhibited maximum impact strength and high resistance to tape water , so we choose this volume fraction to use the epoxy composite in coating . Optical microscopic observations are taken to develop a better understanding of the phenomena taking place in the material system at microscopic level .